Mitigating hydrodynamic ram effect by a novel perforated lattice filled tank. (January 2023) - Wang, Binwen; Zhang, Yu; Bai, Chunyu; Xi, Xulong; Yang, Xianfeng; Yang, Jialing
Abstract: High-velocity impact on fluid-filled structures has become an increasingly critical issue for the vulnerability of aircraft fuel tanks. Hydrodynamic Ram (HRAM) is a typical phenomenon that occurs when a flying object impacts against a fluid-filled tank with a high velocity, leading to excessive structural damage and catastrophic failure. Thus, an effective HRAM mitigation method is highly desired to provide better protection for the aircraft fuel tanks. In this paper, a novel perforated lattice filled tank was proposed by filling the empty space inside a fuel tank to mitigate HRAM effect and reduce the shock wave pressure. Perforated lattices were utilized to reduce the cavity expansion and structural damage while the holes on the lattice walls could guarantee the connectivity for each unit cells. Experimental tests were conducted to investigate the impact response and cavity evolution of the perforated lattice filled tanks with 1 × 1, 3 × 3 and 5 × 5 unit cells. The deformations of the front, back and lateral walls of the lattice-filled tanks were recorded by using a high-speed video camera and strain gauges (SG). Besides, A fluid–structure interaction finite element model of the fuel tank based on the SPH method was established to study the mitigation performance of HRAM phenomenon. A parametric analysis was conducted to explore the influence of unit-cell number, impact velocity, volume fraction of fluid and liquid level pressure on the impact response. The results indicated that the structural deformation and damage can be alleviated by the lattice-filled design, and it could be considered as an effective solution to mitigate the HRAM effect. Highlights: A novel perforated lattice-filled tank was proposed to mitigate HRAM effect and reduce the shock wave pressure. The impact response and cavity evolution of the lattice filled tanks with 1 × 1, 3 × 3 and 5 × 5 unit cells were investigated by dynamic impact tests. The cavity evolution was constrained when it came into contact with the internal lattice panels. With more unit cells filled in a tank, the pressure transmitted to the lateral external wall was smaller. The peak strains on the lateral walls of the 3 × 3 and 5 × 5 lattice filled tanks decreased respectively by 11.9% and 36.4% compared with that of the 1 × 1 lattice filled tanks.